High-resolution isotopic evidence of specialised cattle herding in the European Neolithic - Gerling, Claudia; Doppler, Thomas; Heyd, Volker; Knipper, Corina; Kuhn, Thomas; Lehmann, Moritz F.; Pike, Alistair W. G.; Schibler, Jörg (PLOS ONE, 2017)
Reconstructing stock herding strategies and land use is key to comprehending past human social organization and economy. We present laser-ablation strontium and carbon isotope data from 25 cattle (Bos taurus) to reconstruct mobility and infer herding management at the Swiss lakeside settlement of Arbon Bleiche 3, occupied for only 15 years (3384–3370 BC). Our results reveal three distinct isotopic patterns that likely reflect different herding strategies: 1) localized cattle herding, 2) seasonal movement, and 3) herding away from the site year-round. Different strategies of herding are not uniformly represented in various areas of the settlement, which indicates specialist modes of cattle management. The pressure on local fodder capacities and the need for alternative herding regimes must have involved diverse access to grazing resources. Consequently, the increasing importance of cattle in the local landscape was likely to have contributed to the progress of socio-economic differentiation in early agricultural societies in Europe.